HeXie management theory and sustainable development - He, H. (2012)
The sustainable development between human and nature is the scientific development view laid down and emphasized in the Third Plenary Session of the Sixteenth Central Committee of Chinese Party. This paper looks for preliminary ideas on frameworks for analysing sustainbale development. It first discusses the concept of sustainable development and the potential contradictions of three pillars of sustainability on the basis of the evironment protection, economic development and social progress. Based on this conceptualisation of sustainable development, it then goes on to introduce the latest management tool, HeXie Management Theory and “Dual-Principles” mechanism. Through questionnaires and data analysis we demenstrates HeXie management theory is an adequte tool combining the both aspects of strengthening government management and inspiriting enterprise subjective initiative to solve these internal interacting contradictions and to achieve the sustainable development simultaneously.